2018
DOI: 10.15294/dp.v13i1.15045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Think Pair Share and Two Stay Two Stray Learning Model Towards Learning Outcomes and Cooperation Ability

Abstract: This research aimed to find out the effectiveness of Think Pair Share (TPS) and Two Stay Two Stray (TSTS) methods in improving student learning outcomes and cooperation skills. The population in this research were all students of class X IPS SMA N 2 Banguntapan in the academic year 2016/2017 which consisted of 98 people, divided into four parallel classes. The sampling technique is cluster sampling to classify the students into three classes, divided in experiment class 1, experiment 2, and control class which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…It was mean that not only intelligent students who often participate in learning but students who are less smart often participate in learning too. This happened because lesson study assited Two Stay Two Stray (TSTS) maked the learning more enjoyable, created their ideas and shared with their friends in groups to achieve their learning goal in which they work together to share their understanding about the text, of course, the topics which were related to academic materials (Hidayat & Muhson, 2018). TSTS was a cooperative learning model that can improve student activeness (Wardana, Setyani, & Harwida, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was mean that not only intelligent students who often participate in learning but students who are less smart often participate in learning too. This happened because lesson study assited Two Stay Two Stray (TSTS) maked the learning more enjoyable, created their ideas and shared with their friends in groups to achieve their learning goal in which they work together to share their understanding about the text, of course, the topics which were related to academic materials (Hidayat & Muhson, 2018). TSTS was a cooperative learning model that can improve student activeness (Wardana, Setyani, & Harwida, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Two Stay Two Stray (TSTS) was a technique that divided students into several groups, a group contains four students, two students stay to receive visitor from other groups and two students stray to the other groups. Two Stay Two Stray (TSTS) maked learning more enjoyable, created their ideas and shared with their friends in groups to achieve their learning goal in which they work together to share their understanding about the text, of course, the topics which were related to academic materials (Hidayat & Muhson, 2018). TSTS was a cooperative learning model that can improve student activiness and learning outcomes (Hidayat & Muhson, 2018, & Wardana, Setyani, & Harwida, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous researches showed that implementation of two stay two stray (TSTS) technique could improve reading comprehension for students, and it is effective in teaching reading comprehension (Rasdiana et al, 2019;Saputra, 2016;Suwangsih et al, 2019;Torres & Constain, 2009;Wardana et al, 2018), and it plays the role of a stimulant in the teaching and learning process (Akhiruddin;Sujarwo, 2020). This research is supported by Hidayat & Muhson's (2018) research results that the students who were taught by TPS and TSTS methods were also proven to have better collaborative skills than students taught by conventional methods. Then the results of students 'mathematics learning through cooperative learning model Two Stay Two Stray (TSTS) higher than the results of students' mathematics learning through direct learning model (Nurhusain, 2017), and the TSTS learning model is assisted by an effective mind mapping method to the science learning outcomes (Rahayu et al, 2020).…”
Section: Introductionmentioning
confidence: 88%
“…Pendukung lain yaitu penelitian Hidayat & Muhson (2018), yang hasil penelitiannya menunjukkan bahwa metode TPS dan TSTS terbukti lebih efektif meningkat daripada konvensional terhadap hasil belajar. Siswa yang dibimbing melalui metode TPS serta TSTS yang terbukti memiliki keterampilan kolaborasi yang sangat baik dibanding siswa yang dibimbing dengan metode konvensional (langsung).…”
Section: Pertemuan IIunclassified